BBT 303/3 - Plant Molecular Biology [Bio/ogi Mo/ekul Tumbuhan] - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2008)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2008/2009 April/Mei 2009 BBT 303/3 - Plant Molecular Biology [Bio/ogi Mo/ekul Tumbuhan] Duration: 3 hours [Masa : 3' jam]